Oligodendroglioma with Sarcomatous Transformation: Case Report and Literature Review - Figueiredo, Gonçalo Cerdeira; Pinheiro, Célia Maria; Calheiros, Alfredo Luís (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Oligodendrogliomas are infiltrative tumors of the central nervous system considered to be morphologically stable and to offer a better prognosis. Here, we describe the case of a 36-year-old man with an initial diagnosis of oligodendroglioma, World Health Organization (WHO) grade II, who presented transformation to a sarcomatous form, while maintaining the oligodendroglial component as well as the genetic characteristics of the initial tumor without having undergone any complementary treatments previously. Despite the favorable genetic characteristics, the tumor presented poor response to complementary treatments, and rapid progression, including spinal metastasis.
Keywords: oligodendroglioma; oligosarcoma; co-deletion 1p/19q; spinal metastasis